In situ Rb–Sr geochronology records multiple fluid pulses in Neoproterozoic sequences from the Lubambe-Mingomba Cu deposits in the Zambian Copperbelt - Victor Ikechukwu Vincent; Koen Torremans; Darwinaji Subarkah; Sarah E. Gilbert; Juraj Farkaš; Alan S. Collins; Jon Stacey; Aileen L. Doran; Simon Jones; Murray W. Hitzman (Precambrian Research, 2026)

Sediment-Macrophyte Interactions in Heavy Metal Contaminated Lakes: Insights into Bioaccumulation and Phytoremediation Potential - Gilbert Ndatimana; Unique N. Keke; Diana Nantege; Victoria I. Chukwuemeka; Simon Action; Attobla F. Assie; Auta Y. Iliya; Suleiman M. Abdullahi; Adesola V. Ayanwale; Francis O. Arimoro (Water, Air, & Soil Pollution, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Microplastic impacts on soil and sediment bioturbation: insights from microcosm experiments across diverse ecosystems - Mohammad Wazne; Franck Gilbert; Manon Vallier; Caroline Lise; Solenn Bailly; Stefan Krause; Laurent Simon; Yvan Capowiez; Florian Mermillod-Blondin; Camille Larue (Environmental Pollution, 2026)

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

Assessing the effects of thermo-oxidation and naturally-occurring trace metal ions on the peroxidative susceptibilities of unrefined and refined sunflower oils: An 1H NMR-coupled chemometrics study - Gilbert Ampem; Adam Le Gresley; Martin Grootveld; Simon De Mars; Declan P. Naughton (Food Research International, 2025)

Paleoenvironmental records across middle to Upper Cretaceous in central part of the West and Central African Rift System: Palynological and geochemical inferences - André Mbabi Bitchong; Serge Alberto Bitjong; Serge Parfait Koah Na Lebogo; Glwadys Ngo Mandeng; Cecile Olive Mbesse; Soukaina Obad; Gilbert-François Ngon Ngon; Simon Ngos III; Thierry Adatte (Palaeoworld, 2025)

Exploring macroinvertebrate traits along anthropogenic disturbed gradient in West African Savanna River systems: A case study of Niger state, North central region of Nigeria - Attobla Fulbert Assie; Francis O. Arimoro; Diana Nantege; Gilbert Ndatimana; Simon Action; Unique N. Keke; Adesola V. Ayanwale; Edia O. Edia (Biologia, 2025)

Growth and metabolic performance of house fly and black soldier fly larvae differ across densities and waste-based growth substrates - Asmus Toftkær Muurmann; Niels Thomas Eriksen; Jacob Agerbo Rasmussen; Morten T. Limborg; Jeffery K. Tomberlin; M.Thomas P. Gilbert; Simon Bahrndorff (Waste Management, 2025)

Petrogenesis of cassiterite-rich greisens from Guengue hill, Mayo Darlé, Northwestern Cameroon - Pemha Nyemb Sayom; Bravo Martin Mbang Bonda; Bayiga Elie Constantin; Mbai Simon Joel; Ngon Ngon Gilbert François; Nono Foudje Romaric Noël; Essono Eric; Etame Jacques (Ore and Energy Resource Geology, 2024)

Framework for valorizing waste- and by-products through insects and their microbiomes for food and feed - Asmus Toftkær Muurmann; Marija Banovic; M. Thomas P. Gilbert; Giovanni Sogari; Morten Tønsberg Limborg; Thomas Sicheritz-Pontén; Simon Bahrndorff (Food Research International, 2024)

Correction to: Added diagnostic value of 16S rRNA gene pan-mycobacterial PCR for nontuberculous mycobacterial infections: a 10-year retrospective study - Simon Andenmatten; Onya Opota; Jessica Mazza-Stalder; Laurent Nicod; Gilbert Greub; Katia Jaton (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Potential Use of the Bakari (Adamawa–Cameroon) Quartzites as Sand Filters - Gilbert François Ngon Ngon; Michele Tatiana Minkoe; Zenon Itiga; Darman Japhet Taypondou; Oumar Oumla Kankao; Joel Simon Mbaï; Bravo Martin Mbang Bonda (Geotechnical and Geological Engineering, 2024)

Stream ecosystem puzzle: understanding how water column and sediment variables shape macroinvertebrate patterns in some Afrotropical streams - Simon Action; Francis O. Arimoro; Fulbert A. G. J. Assie; Diana Nantege; Gilbert Ndatimana; Unique N. Keke (Environmental Monitoring and Assessment, 2024)

Development of lake macroinvertebrate-based multimetric index for monitoring ecological health in North Central Nigeria - Gilbert Ndatimana; Francis O. Arimoro; Victoria I. Chukwuemeka; Fulbert A.G.J. Assie; Simon Action; Diana Nantege (Environmental Monitoring and Assessment, 2023)

Mineralogical and geochemical characterization of weathered materials in the gold-bearing quartz veins, Mintom area, Southern Cameroon - Manfred Aurélien Mbenoun; Gilbert François Ngon Ngon; Gildas Tchameni Ngouabe; Michel Bertrand Mbog; Joël Simon Mbaï; Paul Bilong (Arabian Journal of Geosciences, 2023)

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Palynology, mineralogy and geochemistry of sediments in Tondè locality, northern part of Douala sub-basin, Cameroon, Central Africa: implication on paleoenvironment - André Mbabi Bitchong; Thierry Adatte; Gilbert-François Ngon Ngon; Simon Ngos; Paul Bilong (Geosciences Journal, 2021)

Differential Response of Promiscuous Soybean to Local Diversity of Indigenous and Commercial Bradyrhizobium Inoculation Under Contrasting Agroclimatic Zones - Simon Wambui Mburu; Gilbert Koskey; Ezekiel Mugendi Njeru; Omwoyo Ombori; John M. Maingi; Jacinta Malia Kimiti (International Journal of Plant Production, 2020)

Added diagnostic value of 16S rRNA gene pan-mycobacterial PCR for nontuberculous mycobacterial infections: a 10-year retrospective study - Simon Andenmatten; Onya Opota; Jessica Mazza-Stalder; Laurent Nicod; Gilbert Greub; Katia Jaton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)
The diagnosis of mycobacterial infections has been dramatically improved by the introduction of molecular methods aimed to reduce the time to diagnosis as compared with culture. The broad range pan-mycobacterial PCR can detect all the mycobacterial species directly from clinical specimens. We aimed to evaluate its usefulness and its clinical added value for the diagnosis of nontuberculous mycobacterial (NTM) infections. We performed a retrospective study (2003–2013) including 952 samples taken from 639 patients with clinical suspicion of NTM infection. The performance of smear microscopy, PCR and culture was established using clinical data to investigate discrepant results. We also compared the time to microbial diagnosis between the direct PCR and culture. The sensitivity, specificity, positive and negative predictive values of the PCR were 61.6% (53.5–69.1), 99.1% (98.2–99.6), 92.8% (85.8–96.5) and 93.4% (91.6–94.9), respectively, when considering all specimens. When considering smear-positive specimens and smear-negative specimens, the sensitivity was 81.6% and 40%, respectively. The sensitivity for pulmonary and extra-pulmonary smear-positive specimens was 85.2% versus 72.7%. The median time to identification at species level was 35 days (SD, 17.67) for culture and 6 days (SD, 2.67) for the PCR (when positive), which represents a 29-day shorter time to results ( p < 0.0001). The 16S rRNA gene pan-mycobacterial PCR displays a substantial benefit in terms of time to diagnose NTM infections when compared with culture. Despite an excellent specificity, its sensitivity is yet limited in particular for smear-negative specimens, which might be improved by relying onto real-time PCRs.

DNA metabarcoding—Need for robust experimental designs to draw sound ecological conclusions - Lucie Zinger; Aurélie Bonin; Inger G. Alsos; Miklós Bálint; Holly Bik; Frédéric Boyer; Anthony A. Chariton; Simon Creer; Eric Coissac; Bruce E. Deagle; Marta De Barba; Ian A. Dickie; et al. (Molecular Ecology, 2019)

Power analysis as a tool to identify statistically informative indicators for monitoring coral reef disturbances - Simon Van Wynsberge; Antoine Gilbert; Nicolas Guillemot; Tom Heintz; Laura Tremblay-Boyer (Environmental Monitoring and Assessment, 2017)

Drivers of density for the exploited giant clam Tridacna maxima : a meta‐analysis - Simon Van Wynsberge; Serge Andréfouët; Nabila Gaertner‐Mazouni; Colette C C Wabnitz; Antoine Gilbert; Georges Remoissenet; Claude Payri; Cécile Fauvelot (Fish and Fisheries, 2016)
Giant clam populations have been over‐exploited throughout their range over the past decades for their meat and shells. Tridacna maxima, commonly known as the ‘small giant clam’, has remained relatively untargeted by fishers in areas where larger species occur (e.g. Tridacna squamosa ), and high densities of the species are still observed on some isolated and enclosed reefs of the Central Pacific. However, it is unclear whether reported discrepancies in densities worldwide reflect differences in fishing pressure only or a combination of differences in exploitation levels and environmental forcing. We reviewed T. maxima surveys throughout its range to (i) identify patterns of density at global scale, site scale (e.g. island) and intrasite scale; (ii) discuss the influence of sampling method on density estimates; and (iii) identify the primary drivers of giant clam density along gradients of human pressure and natural forcing. We found 59 studies that reported density estimates for 172 sites across 26 countries in the Indo‐Pacific and Red Sea. At intrasite scale, densities were strongly dependent on sampling protocols and surveyed habitats. At site scale, we found close links between T. maxima density and human population per reef area, suggesting that isolated reefs where exploitation only recently started may be more vulnerable to stock collapse in the future. Density patterns were also found to vary significantly depending on reef type (e.g. atoll, island, continental coastline). We discuss how natural processes and fishing pressure may control population dynamics and densities among sites, and make recommendations for future research.

Geographic and temporal dynamics of a global radiation and diversification in the killer whale - Phillip A. Morin; Kim M. Parsons; Frederick I. Archer; María C. Ávila‐Arcos; Lance G. Barrett‐Lennard; Luciano Dalla Rosa; Sebastián Duchêne; John W. Durban; Graeme M. Ellis; Steven H. Ferguson; John K. Ford; Michael J. Ford; et al. (Molecular Ecology, 2015)
Global climate change during the Late Pleistocene periodically encroached and then released habitat during the glacial cycles, causing range expansions and contractions in some species. These dynamics have played a major role in geographic radiations, diversification and speciation. We investigate these dynamics in the most widely distributed of marine mammals, the killer whale ( Orcinus orca ), using a global data set of over 450 samples. This marine top predator inhabits coastal and pelagic ecosystems ranging from the ice edge to the tropics, often exhibiting ecological, behavioural and morphological variation suggestive of local adaptation accompanied by reproductive isolation. Results suggest a rapid global radiation occurred over the last 350 000 years. Based on habitat models, we estimated there was only a 15% global contraction of core suitable habitat during the last glacial maximum, and the resources appeared to sustain a constant global effective female population size throughout the Late Pleistocene. Reconstruction of the ancestral phylogeography highlighted the high mobility of this species, identifying 22 strongly supported long‐range dispersal events including interoceanic and interhemispheric movement. Despite this propensity for geographic dispersal, the increased sampling of this study uncovered very few potential examples of ancestral dispersal among ecotypes. Concordance of nuclear and mitochondrial data further confirms genetic cohesiveness, with little or no current gene flow among sympatric ecotypes. Taken as a whole, our data suggest that the glacial cycles influenced local populations in different ways, with no clear global pattern, but with secondary contact among lineages following long‐range dispersal as a potential mechanism driving ecological diversification.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

The relation between adiposity throughout the life course and variation in IGFs and IGFBPs: evidence from the ProtecT (Prostate testing for cancer and Treatment) study - Mari-Anne Rowlands; Jeff M. P. Holly; David Gunnell; Rebecca Gilbert; Jenny Donovan; J. Athene Lane; Gemma Marsden; Simon M. Collin; Freddie Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2010)

Potential for phosphonoacetate utilization by marine bacteria in temperate coastal waters - Jack A. Gilbert; Simon Thomas; Natalie A. Cooley; Anna Kulakova; Dawn Field; Tim Booth; John W. McGrath; John P. Quinn; Ian Joint (Environmental Microbiology, 2009)
Summary Phosphonates are organic compounds that contain a C–P bond and are a poorly characterized component of the marine phosphorus cycle. They may represent a potential source of bioavailable phosphorus, particularly in oligotrophic conditions. This study has investigated the distribution of the phnA gene which encodes phosphonoacetate hydrolase, the enzyme that mineralizes phosphonoacetate. Using newly designed degenerate primers targeting the phnA gene we analysed the potential for phosphonoacetate utilization in DNA and cDNA libraries constructed from a phytoplankton bloom in the Western English Channel during July 2006. Total RNA was isolated and reverse transcribed and phosphonoacetate hydrolase ( phnA ) transcripts were PCR amplified from the cDNA with the degenerate primers, cloned and sequenced. Phylogenetic analysis demonstrated considerable diversity with 14 sequence types yielding five unique phnA protein groups. We also identified 28 phnA homologues in a 454‐pyrosequencing metagenomic and metatranscriptomic study from a coastal marine mesocosm, indicating that > 3% of marine bacteria in this study contained phnA . phnA homologues were also present in a metagenomic fosmid library from this experiment. Finally, cultures of four isolates of potential coral pathogens belonging to the Vibrionaceae contained the phnA gene. In the laboratory, these isolates were able to grow with phosphonoacetate as sole P and C source. The fact that the capacity to utilize phosphonoacetate was evident in each of the three coastal environments suggests the potential for widespread utilization of this bioavailable P source.

Variation analysis and gene annotation of eight MHC haplotypes: The MHC Haplotype Project - Roger Horton; Richard Gibson; Penny Coggill; Marcos Miretti; Richard J. Allcock; Jeff Almeida; Simon Forbes; James G. R. Gilbert; Karen Halls; Jennifer L. Harrow; Elizabeth Hart; Kevin Howe; et al. (Immunogenetics, 2008)

Assessment of the Directional Elastic Moduli of Ewe Vertebral Cancellous Bone by Vibrational Testing - Paul S. Weinhold; Simon C. Roe; Jerome A. Gilbert; C. Frank Abrams (Annals of Biomedical Engineering, 1999)